Nurse moral disengagement. (August 2016) - Fida, Roberta; Tramontano, Carlo; Paciello, Marinella; Kangasniemi, Mari; Sili, Alessandro; Bobbio, Andrea; Barbaranelli, Claudio
Background: Ethics is a founding component of the nursing profession; however, nurses sometimes find it difficult to constantly adhere to the required ethical standards. There is limited knowledge about the factors that cause a committed nurse to violate standards; moral disengagement, originally developed by Bandura, is an essential variable to consider. Research objectives: This study aimed at developing and validating a nursing moral disengagement scale and investigated how moral disengagement is associated with counterproductive and citizenship behaviour at work. Research design: The research comprised a qualitative study and a quantitative study, combining a cross-validation approach and a structural equation model. Participants and research context: A total of 60 Italian nurses (63% female) involved in clinical work and enrolled as students in a postgraduate master's programme took part in the qualitative study. In 2012, the researchers recruited 434 nurses (76% female) from different Italian hospitals using a convenience sampling method to take part in the quantitative study. Ethical considerations: All the organisations involved and the university gave ethical approval; all respondents participated on a voluntary basis and did not receive any form of compensation. Findings: The nursing moral disengagement scale comprised a total of 22 items. Results attested the mono-dimensionality of the scale and its good psychometric properties. In addition, results highlighted a significant association between moral disengagement and both counterproductive and citizenship behaviours. Discussion: Results showed that nurses sometimes resort to moral disengagement in their daily practice, bypassing moral and ethical codes that would normally prevent them from enacting behaviours that violate their norms and protocols. Conclusion: The nursing moral disengagement scale can complement personnel monitoring and assessment procedures already in place and provide additional information to nursing management for designing interventions aimed at increasing compliance with ethical codes by improving the quality of the nurses' work environment.